2018
DOI: 10.3177/jnsv.64.379
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Dietary Tempeh Prepared with <i>Rhizopus stolonifer</i> on Liver Function in Rats Fed with a High-Fat Diet

Abstract: The regional standard for tempeh established by the Codex Alimentarius defines the use of Rhizopus oligosporus, R. oryzae, and/or R. stolonifer as soybean tempeh starters. However, comparative studies on the functions of tempeh prepared with these Rhizopus species are scarce. In the present study, we examined the effects of dietary tempeh prepared with these three Rhizopus species using rats fed with a high-fat diet. Compared to the control diet, consumption of tempeh prepared with R. stolonifer significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Addtitionally, tempeh Ro and tempeh Rs have been reported to have significantly higher β-glucosidase activities associated with the production of isoflavone aglycones than tempeh Rm, suggesting higher production of isoflavone aglycones in tempeh Rs (Kameda et al, 2018a). In this study, the daidzein and genistein contents in tempeh Rs were 0.024 and 0.041 g/100 g dry weight, respectively, which were similar to previously reported values (Kameda et al, 2018a;Kameda et al, 2018b). Isoflavone aglycones are known to be absorbed faster and more rapidly than their glucosides (Izumi et al, 2000;Kano et al, 2006).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Addtitionally, tempeh Ro and tempeh Rs have been reported to have significantly higher β-glucosidase activities associated with the production of isoflavone aglycones than tempeh Rm, suggesting higher production of isoflavone aglycones in tempeh Rs (Kameda et al, 2018a). In this study, the daidzein and genistein contents in tempeh Rs were 0.024 and 0.041 g/100 g dry weight, respectively, which were similar to previously reported values (Kameda et al, 2018a;Kameda et al, 2018b). Isoflavone aglycones are known to be absorbed faster and more rapidly than their glucosides (Izumi et al, 2000;Kano et al, 2006).…”
Section: Resultssupporting
confidence: 90%
“…Tempeh is a traditional non-salted soybean food from Indonesia that is fermented by Rhizopus species. Isoflavone aglycones, peptides, free amino acids, and gammaaminobutyric acid are present in larger amounts in tempeh compared to in unfermented soybean (Aoki et al, 2003a;Baumann et al, 1991;Kameda et al, 2018a;Kameda et al, 2018b;Matsumoto and Imai, 1990). Tempeh has various physiological effects, which include modulating the colonic environment (Utama et al, 2013), improving lipid metabolism (Watanabe et al, 2006), promoting calcium absorption (Watanabe et al, 2008), reducing elevated systolic blood pressure in rats (Aoki et al, 2003b), and increasing the amounts of Bifidobacterium and Lactobacillus species in the rat cecum (Yang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Rhizopus stolonifer increased daidzein and genistein levels more than R. oligosporus and R. oryzae by up to twofold (Kameda, Aoki, Yanaka, Kumrungsee, & Kato, 2018). In rats fed with a high‐fat diet, only supplementation of tempeh fermented with R. stolonifer improved liver function by significantly suppressing serum aspartate transaminase, total bilirubin, and ammonium levels (Kameda et al., 2018). Supplementation of R. stolonifer tempeh also improved gut health in rats by increasing the amounts of Bifidobacterium , Lactobacillus , propionate, and acetate, as well as decreasing cecal Enterobacteriaceae and Akkermansia muciniphila levels (Yang et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A novel plasmin with high thrombolytic activity was found in brewed rice wine with Rhizopus chinense 12 (Du et al ., 2005) and traditional Douchi (Wang et al ., 2006; Hu et al ., 2019); thus plasmin has the potential to be a newly anti‐thrombosis therapeutic agent similar to nattokinase. (Sumi et al ., 1990; Omura et al ., 2005) Kameda (Tsuyoshi, et al ., 2018) reported that Douchi, which was fermented by three kinds of Rhizopus chinense 12, has a beneficial effect on the liver function of rats fed with a high‐fat diet. Mung beans (Keong et al ., 2015) and black beans (Oh et al ., 2014) fermented by Monascus pilosus could improve hyperlipidaemia and hypercholesterolaemia.…”
Section: Introductionmentioning
confidence: 99%